2010
DOI: 10.1179/174328810x12814016178917
|View full text |Cite
|
Sign up to set email alerts
|

Daily ambulatory activity monitoring in patients with peripheral artery disease

Abstract: Background: Peripheral artery disease (PAD) is characterized by arterial lesions of the lower extremities. Patients with PAD present ambulatory dysfunction due to intermittent claudication, limiting daily physical activity and increasing morbidity. Therefore, objectively measured daily ambulation is a clinically relevant outcome in these patients. Objective: To quantify daily ambulation with a step activity monitor (Step Watch 3 TM ; Cyma Inc., Mountlake Terrace, WA, USA) in patients with PAD. Major findings: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…Previous studies in subjects without PAD have shown that more advanced age is associated with lower levels of physical activity, which have been attributed to changes in lifestyle after retirement, and the occurrence of comorbid conditions [32][33][34]. Studies in IC patients have suggested that those with comorbid conditions such as diabetes, ischemic heart disease, hypertension, and hyperlipidemia have low levels of physical activity [9,35,36]. The present study corroborates these results, since physical activity was negatively associated with diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies in subjects without PAD have shown that more advanced age is associated with lower levels of physical activity, which have been attributed to changes in lifestyle after retirement, and the occurrence of comorbid conditions [32][33][34]. Studies in IC patients have suggested that those with comorbid conditions such as diabetes, ischemic heart disease, hypertension, and hyperlipidemia have low levels of physical activity [9,35,36]. The present study corroborates these results, since physical activity was negatively associated with diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 94%
“…In response to these causes, a recent review reported that walking capacity and comorbid conditions are associated with low levels of physical activity in IC patients [9]. Furthermore, studies in other populations, such as diabetics and patients with comorbid musculoskeletal pain and depression, have shown an inverse relationship between physical activity levels and personal [12,13] and environmental barriers [14,15], such as lack of time, lack of motivation, low income, lack of places to perform physical activity, and poor weather conditions [16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ABI, considered one of the best prognostic indexes in PAD, 22 and walking capacity, a main clinical marker of PAD associated with endothelial function 23 inflammation 24 and several clinical indicators, 2,25 were not associated with the meeting of physical activity recommendations. These results are not surprising, since ABI 26 and walking capacity have been poorly associated with physical activity in patients with PAD. 27…”
Section: Discussionmentioning
confidence: 68%
“…For example, Shephard and Aoyagi 2 suggest that the minimum habitual physical activity level for elderly individuals to maintain health may be substantially less than that inferred from self-report measures. Gardner et al 3 reviewed objective physical activity data in patients with peripheral arterial disease and concluded that not only are these patients deficient in the volume of activity they take, but that they should be encouraged to walk at a faster cadence (i.e. steps/minute).…”
mentioning
confidence: 99%